Impact of Ramadan Intermittent Fasting on Oxidative Stress Measured by Urinary 15-F2t-Isoprostane - Mo'ez Al-Islam Ezzat Faris; Rand Nidal Hussein; Ref'at Ahmad Al-Kurd; Mohammed Ahmed Al-Fararjeh; Yasser Khalil Bustanji; Mohammad Khalil Mohammad (Journal of Nutrition and Metabolism)
Fasting and caloric restriction have been associated with reduced incidence of chronic diseases and cancers. These effects have been attributed to reduced oxidative stress. Since Ramadan intermittent fasting (RIF) has been associated with reduced caloric intake, it was hypothesized that RIF would alleviate oxidative stress in healthy volunteers. The study was designed to elucidate the impact of RIF on oxidative stress measured by 15-F2t-Isoprostane (15FIP). Fifty healthy subjects (23 men and 27 women) who intended to fast Ramadan were recruited. Urine and serum sampling and anthropometric and dietary assessments were conducted one week before Ramadan (T0), at the end of the third week of Ramadan (T1), and one month after Ramadan (T2). Biochemical measurements included urinary 15FIP, creatinine, and hematological indices. Results revealed that the urinary level of 15FIP measured at T0 was normal, while they showed a significantly (P<0.05) higher level when measured at T1 concomitant with a significant (P<0.05) increase in the body weight and total body fat percent. In conclusion, results suggest that increased body weight is associated with increased lipid peroxidation and oxidative stress, and the impact of RIF on oxidative stress is mediated by the changes in body weight at the end of the month.